Immune restoration in HIV-1-infected patients after 12 years of antiretroviral therapy: a real-world observational study - Jiaye Liu; Lifeng Wang; Yuying Hou; Yan Zhao; Zhihui Dou; Ye Ma; Dawei Zhang; Yasong Wu; Decai Zhao; Zhongfu Liu; Fujie Zhang; Lei Jin; et al. (Taylor & Francis, 2020)
Using normalization of CD4 counts as the main evaluation parameter of complete immune restoration for HIV-1 patients under antiretroviral therapy (ART) might be not enough. A comprehensive evaluation system more accurately reflecting immune restoration are urgently needed. Totally, 91,805 HIV-1 patients from 17 tertiary hospitals in China during 2005–2018 were included in this study. Immune restoration and mortality were assessed. Patients initiated ART with baseline CD4 counts <50, 50–199, 200–349, 350–499, and ≥500 cells/μL, and results showed an increase in the median CD4 counts to 445 (12-year), 467 (12-year), 581 (11-year), 644 (7-year), and 768 cells/µL (5-year), as well as the CD4/CD8 ratio to 0.59 (12-year), 0.65 (12-year), 0.79 (11-year), 0.82 (7-year), 0.9 (5-year), respectively. The median CD8 count was relatively high (median range 732–845 cells/μL), regardless of the baseline CD4 counts. Furthermore, the probabilities of death in patients achieving CD4 counts ≥500 cells/μL and CD4/CD8 ratio ≥0.8 simultaneously were significantly lower than those in patients achieving either CD4 counts ≥500 cells/μL (2.77% vs 3.50%, p=0.02) or CD4/CD8 ≥ 0.8 (2.77% vs 4.28%, p<0.001) after 12-year of ART. In this study, a new binary-indicator would accurately assess immune restoration in the era of “treat all.”
Keywords: Medicine; Biotechnology; Immunology; Biological Sciences not elsewhere classified; Science Policy; Computational Biology